Investigations After Death in Children. (August 2018) - Bohn, Desmond; Chiasson, David; Huyer, Dirk
Abstract : Objectives: To discuss the role of investigations after death in children as part of a supplement on "Death and Dying in the PICU." Data Sources: Literature review, personal experience, and expert opinion. Data Selection: Not applicable. Data Extraction: Moderated by three experts on investigations after death in children. Data Synthesis: Not relevant. Conclusions: A multidisciplinary cliniciopathologic conference is important after the death of a child in order to help bring closure to the family and to attempt to address any concerns they may have about the care. It is also an important part of the quality of care process for a tertiary care institution and provides an unique opportunity for ongoing medical education. The model of a multidisciplinary cliniciopathologic conference used by the Ontario Coroner's Office to investigate sudden and unexpected deaths in children under 5 years old, which has been functioning for over 30 years, is described. Reports from this Pediatric Death Review Committee have been influential in improving the care of children in the province of Ontario.